Prevalence of 16S rRNA methylase, modifying enzyme, and extended-spectrum beta-lactamase genes among Acinetobacter baumannii isolates. (August 2015) - Liu, Zhenru; Ling, Baodong; Zhou, Liming
<x content-type="archive" xml:space="preserve">Abstract</x> Multidrug-resistant Acinetobacter baumannii has become a worldwide problem, and methylation of 16S rRNA has recently emerged as a new mechanism of resistance to aminoglycosides, which is mediated by a newly recognized group of 16S rRNA methylases. 16S rRNA methylase confers a high-level resistance to all 4, 6-substituted deoxystreptamine aminoglycosides that are currently used in clinical practice. Some of the A. baumannii isolates have been found to coproduce extended-spectrum beta-lactamases (ESBLs), contributing to their multidrug resistance. The aim of this study was to detect the determinants of the 16S rRNA methylase genes armA, rmtA, rmtB, rmtC, rmtD, rmtE, and npmA, the modifying enzyme genes aac(6′)-Ib, ant(3″)-Ia, aph(3′)-I, and the extended-spectrum beta-lactamase genes blaTEM, blaSHV, and blaCTX-M-3 among A. baumannii isolates in northeastern Sichuan, China. Minimum inhibitory concentrations (MICs) of 21 different antimicrobial agents against the A. baumannii isolates were determined. The clinical isolates showed a high level of resistance (MIC≧256 μg/ml) to aminoglycosides, which ranged from 50·1 to 83·8%. The resistances to meropenem and imipenem, two of the beta-lactam antibiotics and the most active antibiotics against A. baumannii, were 9·1 and 8·2%, respectively. Among 60 amikacin-resistant isolates, only the 16S rRNA methylase gene armA was found to be prevalent (66·7%), but the other 16S rRNA methylase genes rmtA, rmtB, rmtC, rmtD, rmtE, and npmA were not detected. The prevalences of the modifying enzyme genes aac (6′)-Ib, ant (3″)-Ia, and aph (3′)-I were 51·7, 81·7, and 58·3%, respectively, which are different from a previous study in which the occurrences of these genes were 3, 64, and 72%, respectively. Among the 40 isolates that were armA-positive, the prevalences of blaTEM, blaSHV, and blaCTX-M-3 genes were detected for the first time in China, and their occurrences were 45, 65, and 52·5%, respectively. In all, A. baumannii with all the 16S rRNA methylase, modifying enzyme, and ESBL genes is extremely prevalent in northeastern Sichuan, China, posing a serious clinical concern with a major therapeutic threat in the future.